2019
DOI: 10.1186/s12909-019-1804-7
|View full text |Cite
|
Sign up to set email alerts
|

Medical students’ perception on fecal microbiota transplantation

Abstract: Background Fecal microbiota transplantation (FMT) has become an emergent method in the therapy of several intestinal diseases, mainly in Clostridium difficile recurrence. The training of FMT in medical schools is at its beginning and in countries where FMT is only occasionally carried out, it is important to know the perception of medical students on FMT. Methods We undertook a survey of 3rd year medical students not exposed to offic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…It may also impact the likelihood of doctors to discuss this procedure with their patients. A survey found that 69% of medical students believed it would be easier to discuss FMT with patients if it had a more socially acceptable name 6 . We believe that the meaning of “intestinal” vs “faecal” does not significantly differ in this context and it could be used as a more appealing substitute that reduces stigma associated with the source of the donor material.…”
Section: Existing Proposedmentioning
confidence: 90%
See 1 more Smart Citation
“…It may also impact the likelihood of doctors to discuss this procedure with their patients. A survey found that 69% of medical students believed it would be easier to discuss FMT with patients if it had a more socially acceptable name 6 . We believe that the meaning of “intestinal” vs “faecal” does not significantly differ in this context and it could be used as a more appealing substitute that reduces stigma associated with the source of the donor material.…”
Section: Existing Proposedmentioning
confidence: 90%
“…A survey found that 69% of medical students believed it would be easier to discuss FMT with patients if it had a more socially acceptable name. 6 We believe that the meaning of "intestinal" vs "faecal" does not significantly differ in this context and it could be used as a more appealing substitute that reduces stigma associated with the source of the donor material. This change has been suggested previously to overcome the negative connotations and confusion surrounding the use of "faecal".…”
mentioning
confidence: 91%
“…In Romania, isolated cases successfully managed using FMT [9] and one prospective study comprising 30 patients with recurrent CDI [10] was reported. Moreover, a recent study performed in one tertiary center in Romania revealed some aspects regarding FMT perception among medical students that require improvement [11]; consequently, better knowledge on this procedure needs to be promoted among Romanian practitioners.…”
Section: Rationale Of the National Guideline T H E E P I D E M I O L mentioning
confidence: 99%
“…Similarly, medical sciences students in Iran also had adequate general knowledge about probiotics, but their awareness of commercially available products and, consequently, their consumption of these items was low [ 21 ]. Concerning FMT, a survey of medical students in Romania revealed that only one-third of the participants had an acceptable level of knowledge about this procedure [ 22 ]. FMT knowledge in a large cohort of Chinese medical students also appeared to be insufficient [ 23 ].…”
Section: Introductionmentioning
confidence: 99%